Plea for Change of Models for Marriage (Hekima Review, 2009)
Since they first began evangelising in Sub-Saharan Africa, one of the most troublesome topics confronting missionaries was the question of marriage. Polygamy and so-called African traditional marriages, and the scandal these issues caused, were a great problem for the early missionaries.